The determinants of thinly capitalized tax avoidance structures: Evidence from Australian firms - Taylor, Grantley; Richardson, Grant (Pergamon, 2013)
This paper examines the determinants of thinly capitalized structures of publicly-listed Australian firms. Based on a hand-collected sample of 203 publicly-listed Australian firms over the 2006–2009 period (812 firm-years), our regression results indicate that the thin capitalization position of firms is significantly and positively associated with multinationality, tax haven utilization, withholding taxes and tax uncertainty. Multinationality and the use of tax havens are, in particular, strongly associated with thin capitalization. Our additional regression results provide evidence that shows that corporate governance monitoring mechanisms relating to board of director independence, institutional ownership andbig-4 auditor utilization are significantly negatively associated with firms adopting thinly capitalized tax avoidance structures.